2017
DOI: 10.1111/dmcn.13651
|View full text |Cite
|
Sign up to set email alerts
|

Educational outcomes for children with cerebral palsy: a linked data cohort study

Abstract: From 2009 to 2014, most Australian children with cerebral palsy (CP) attended a mainstream school. The rate of disability-related exemption from standardized educational testing was almost 50%. Thirty per cent of children with CP achieved educational scores in the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 16 publications
3
30
1
Order By: Relevance
“…Children who developmentally vulnerable are more likely to have poor educational outcomes in primary school and early high school 5 6. As adults, these inequities widen, presenting as higher levels of morbidity and mortality, lower levels of academic achievement, poorer employment opportunities and reduced participation in society 7–9…”
Section: Introductionmentioning
confidence: 99%
“…Children who developmentally vulnerable are more likely to have poor educational outcomes in primary school and early high school 5 6. As adults, these inequities widen, presenting as higher levels of morbidity and mortality, lower levels of academic achievement, poorer employment opportunities and reduced participation in society 7–9…”
Section: Introductionmentioning
confidence: 99%
“…In our study, 36% of children with CP finished compulsory school fulfilling the requirements to proceed to secondary school. This can be compared with an Australian study in which around 30% of the children with CP scored in the range of population norms in standardized educational testing 14 . In Denmark, around 50% of children with CP had continued studies after lower secondary school, which is equivalent in age to compulsory school in the current study 12 .…”
Section: Discussionmentioning
confidence: 88%
“…Education plays a central role in enabling children and adolescents to participate in the labour market as adults, but it is unknown to what extent low rates of labour market participation are due to lower educational levels among persons with CP. Although level of education has been shown to be lower among adults with CP compared with the general population, 12,13 an Australian study showed that around 30% of children with CP obtained scores in the range of population norms in standardized educational testing 14 . Children with more severe motor symptoms were less likely to undergo educational assessments or to obtain population‐norm scores.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a causal link has been proposed between visuospatial attention and reading acquisition (Hari and Renvall, 2001; Vidyasagar and Pammer, 2010; Franceschini et al, 2012; Collis et al, 2013). In view of the high incidence of reading difficulties in CPC (Frampton et al, 1998; Schenker et al, 2005; Gillies et al, 2018), deficits in selective attention may be responsible also for learning disorders in CP (Bottcher, 2010).…”
Section: Introductionmentioning
confidence: 99%